2014
DOI: 10.4072/rbp.2014.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização palinoflorística e paleoambiental da Formação Santana (Cretáceo Inferior), Poço 4-BO-1-PE, bacia do Araripe, Nordeste do Brasil

Abstract: -PALYNOFLORAL AND PALEOENVIRONMENTAL CHARACTERIZATION OF THE SANTANA FORMATION (LOWER CRETACEOUS), 4-BO-1-PE WELL, ARARIPE BASIN, NORTHEAST BRAZIL.A paleoenvironmental characterization of the Santana Formation sedimentary rocks (4-BO-1-PE well), Araripe Basin, Late Aptian-Early Albian, was accomplished through qualitative and quantitative analyses of the palynofl ora. Palynological and lithological evidence indicate a predominantly continental depositional environment for this section, composed by a fl uvial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
6
0
4
Order By: Relevance
“…For Arens and Allen (2014), Cupressinocladus is a genus characteristic of more drained areas around rivers or deltas, and Alvin (1983) considers that the Cheirolepidiaceae is an indicator of seasonally arid conditions. Thus, as expressed by the types discussed in this study, and from other ones present in the Early Cretaceous floras of Brazil (Duarte & Santos 1993, Ferreira et al 2008, Portela et al 2014, the temporary resistant condition of the vegetation to drought and to hypersaline environments, proposed by Mohr et al (2006), seems to be confirmed and coincides with the evaporitic depositional context of the Codó Formation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…For Arens and Allen (2014), Cupressinocladus is a genus characteristic of more drained areas around rivers or deltas, and Alvin (1983) considers that the Cheirolepidiaceae is an indicator of seasonally arid conditions. Thus, as expressed by the types discussed in this study, and from other ones present in the Early Cretaceous floras of Brazil (Duarte & Santos 1993, Ferreira et al 2008, Portela et al 2014, the temporary resistant condition of the vegetation to drought and to hypersaline environments, proposed by Mohr et al (2006), seems to be confirmed and coincides with the evaporitic depositional context of the Codó Formation.…”
Section: Discussionmentioning
confidence: 56%
“…As previously observed, the Gnetales are an important component in the palynological assemblage of the Codó Formation, the Santana Formation (Portela et al 2014) and the basal Potomac Group (Doyle & Hickey 1976). For Crane and Upchurch Jr. (1987), the absence of extensive secondary tissues in the Gnetales and in Drewria, indicates that it is an herbaceous plant.…”
Section: Remarksmentioning
confidence: 63%
“…A leitura foi realizada em microscópio óptico com câmera fotográfica acoplada (Leyca), onde foram contados todos os palinomorfos presentes, incluindo o marcador exótico. Por conta da ausência de referências de palinomorfos do Cretáceo do Grupo Bauru, foram utilizadas, como auxílio nas identificações, diversas bibliografias do Cretáceo ao Paleoceno de localidades no Brasil (Regali et al 1974;Lima 1982;Coimbra et al 2002;Ferreira et al 2005;Arai and Duarte 2010;Premaor et al 2010;Souza et al 2010;Araújo et al 2011;Ferreira et al 2011Ferreira et al , 2013Oliveira 2011;Duarte et al 2012;Portela et al 2014), outros países da América da Sul (Van der Hammen and Wijmstra 1964;Vajda-Santivanez 1999;Prámparo et al 2007;Ottone 2009;Vallati 2010Vallati , 2013Garzon 2011;Povilauskas 2012Povilauskas , 2013 e do continente africano (McLachlan and Pieterse 1978;Morgan 1978;Kotova, 1978;Masure et al 1998;Atta-Petters and Salami 2006;Eisawi and Schrank 2008;Chiaghanam et al 2012;Eisawi et al 2012;Apaalse and Atta-Peters 2013;Atta-Peters et al 2013;. A concentração de palinomorfos foi calculada para indicar o número de grãos por centímetro cúbico de amostra (Salgado-Labouriau and Rull 1986).…”
Section: Materiais E Métodosunclassified
“…Os representantes atuais e fósseis do gênero Ephedra podem ser pequenas árvores, arbustos ou subarbustos (Yang et al 2005). São plantas de hábito xeromórfico (Portela et al 2014), que faz o gênero Ephedra ser comum na forma de arbusto em ambientes desérticos (Simpson 2006). interna lisa e uma externa ornamentada com "costelas" longitudinais e paralelas, separadas por depressões finas, em número de 15 a 18 por face do grão.…”
Section: Natureza E Morfologia Das Amostrasunclassified
See 1 more Smart Citation